Ultrasound and electric fields as novel techniques for assisting the wine ageing process: The state-of-the-art research - García Martín, Juan Francisco; Sun, Da-Wen (Trends in food science & technology, 2013)
High-quality wines are traditionally produced by ageing them in barrels or bottles. However, these processes are very time-consuming. In recent years, some physical technologies, namely ultrasound and electric fields, have been assayed to accelerate reactions within the wine (ageing techniques) or to increase phenolic compounds extraction from grape to must (extraction techniques), the latter ones improving the further ageing process. On the other hand, their antimicrobial effect should be taken into account when applying during fermentation or immediately afterwards. This paper intends to review current achievements and the potential of ultrasound and electric fields in enhancing the wine ageing process. •Ultrasound and electric fields are novel wine ageing technologies.•Ultrasound increases anthocyanins and decreases tannins in wines.•Electric fields lead to wines with higher content in total phenols.•Both techniques cannot modify basic oenological parameters.